Determination method of stress concentration relief factors for failure prediction of composite multi-bolt joints. (June 2015) - Zhao, Libin; Qin, Tianliang; Zhang, Jianyu; Shan, Meijuan; Fei, Binjun
Stress concentration relief factor, which reflects the linear relationship between the stress concentration factors of composite joint and those of elastic isotropic joint, was proposed by Hart-Smith for the failure prediction of composite multi-bolt joints. It is deemed to be determined by experiments from either unloaded- or loaded-hole laminates and is suitable for investigations of bypass and bearing stress concentration factors. To examine this viewpoint, in this paper, the stress concentration relief factor is determined by tensile tests of open-, filled- and loaded-hole laminates failing in tensile mode, respectively. It can be found that the loaded-hole has obviously high-stress concentration level, while the filled-hole has slightly higher stress concentration than that of open-hole. Detailed 3D-FE analyses are performed to disclose the stress concentration mechanisms of three hole-laminates. Various stress concentration relief factors are combined to calculate bearing and bypass stress concentration factors, which provide the failure envelope for the strength prediction of composite joints. Moreover, both conventional and modified failure envelopes are discussed. Experimental results of two-, three- and four-bolt joints are provided to investigate the suitability of different failure envelopes. It follows that the stress concentration relief factor for bearing stress concentration factor needs to be determined by a loaded-hole laminate, while that for bypass stress concentration factor can be determined by each of open-, filled- and loaded-hole laminates.